Desvelando a vergonha da vivência de trecheiros na contemporaneidade - Soldera, Lucas Martins [UNESP]; Hashimoto, Francisco [UNESP] (My University, 2012)
This research aimed at identifying the existence of the feeling of shame in “trecheiros” (nomads) in the contemporary world and which meanings were built in those people’s lives. Such comprehension was developed based on the questioning regarding the subject, its history, and its relation with the group and with society. The survey was based on the psychosociological approach and the material was built with reports from eight “trecheiros” who use the services of the C.A.M. (Migrants’ Assistance Center) of Assis, in the State of São Paulo. The data were gathered by means of semidirected interviews, with varied lengths of time. The survey enabled the comprehension of the meanings built by the “trecheiros” from the three aspects which identify this contemporary: the registrations of the body, of the action, and of the feeling. Finally, the feeling of shame was found related to these three aspects, marking the relation of uneasiness between shame and contemporary.

Este trabalho visou a identificar a presença do sentimento da vergonha em “trecheiros” (nômades) no mundo contemporâneo e quais significados foram construídos na vida dessas pessoas. Efetuou-se tal compreensão a partir do questionamento sobre o sujeito, a sua história e a sua relação com o grupo e com a sociedade. A pesquisa se fundamentou na abordagem Psicossociológica, e o material de estudo foi constituído por relatos de sete “trecheiros” que fazem uso dos serviços do Centro Atendimento ao Migrante (CAM) de Assis/SP. Os dados foram obtidos por meio de entrevistas semidirigidas com duração variável. A pesquisa possibilitou a compreensão das significações construídas pelos trecheiros a partir dos três aspectos que identificam esse contemporâneo: o registro do corpo, da ação e do sentimento. Por fim, foi encontrado o sentimento da vergonha relacionado a esses três aspectos, marcando a relação de mal-estar entre vergonha e contemporâneo.
Unveiling the shame of “trecheiros” experiences in the contemporary world
Keywords: Shame; Psychosociology; Comtemporary; Nomads; Vergonha; Psicossociologia; Contemporaneidade; Nômades